LEGAL CERTAINTY REGARDING THE POSITION OF ILLEGITIMATE CHILDREN WHO ARE RECOGNIZED LEGITIMATELY AS SUBSTITUTE HEIRS (PLAATSVERVULLING) - Aditya Syahrul Ikram; Abdul Rachmad Budiono; Yenny Eta Widyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The position of illegitimate children who are legally recognized as Substitute Heirs (Plaatsvervulling) in Indonesia is still not fully regulated. The position of illegitimate children who are recognized as legal if they replace their parents still often causes conflict, especially the conflict that occurs between Article 872 of the Civil Code and the Constitutional Court Decision. Number 46/PUU-VIII/2010 which amends Article 43 paragraph (1) of the Marriage Law. The existence of this conflict will certainly give rise to legal uncertainty so this needs to be studied. This research will discuss legal certainty regarding the position of illegitimate children who are recognized as legal successors (Plaatsvervulling). This research is a normative juridical research method with the approach taken being a statutory approach. The results of the analysis of legal uncertainty regarding the position of illegitimate children who are recognized as legal substitute heirs (Plaatsvervulling) can be resolved using the principle of lex posterior derogat legi priori, so that the Marriage Law overrides the law of the Civil Code, so that illegitimate children have the right to become successor heirs to their parents without Look at the terms or conditions as stated in Article 873 of the Civil Code.